(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the clinical and radiological outcomes of freehand patellar resection technique versus cutting guide technique in primary total knee arthroplasty. Methods: This randomized controlled trial was conducted in the Institute of Orthopaedics and Surgery Karachi from 1st February 2019 to 1st July 2020. All patients with primary total knee arthroplasty (TKA) fulfilling the inclusion criteria were divided randomly into patellar resection with freehand technique(group A) and cutting guide technique(group B).The post operative clinical and radiological parameters were compared in both groups and P value was calculated with Chi-square test for statistical significance. P value< 0.05 was considered significant. Results: The total number of patients in our study were 114 divided equally into group A and group B with 57 patients each. In group A male patients were 24(42, 1%) and female 33(57.8%). In group B male patients were 21(36.8%) and female 36(63.1%).The mean age of group A patients was 57.00 ± 5.60 and group B 57.65 ± 5.55 years. Post operatively slightly lesser frequency of patients had positive patellar glide test, patellar grind test, patellar edge tenderness and anterior knee pain in group A than in group B(P>0.05). No statistically significant difference in the mean values of lateral patellar tilt(LPT), lateral patellar displacement(LPD), Insall-Salvati (IS) index and hip knee ankle(HKA) angle and their outliers in both the groups were noted.(P>0.05). Conclusion: Identical clinical and radiological results were achieved by both free hand patellar resection technique and cutting guide technique. Freehand patellar resection technique however had slightly lower but not significant positive patellofemoral tests and anterior knee pain than cutting guide technique.